General principles of European community law : reports from a conference in Malmö, 27-28, August 1999 : organised by the Swedish Network for European Legal Studies and the Faculty of Law, University of Lund /: reports from a conference in Malmö, 27-28, August 1999 : organised by the Swedish Network for European Legal Studies and the Faculty of Law, University of Lund. (2000) - Unknown
No abstract available